2009
DOI: 10.3892/ijo_00000321
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome analysis of hepatitis B virus-associated small hepatocellular carcinoma by serial analysis of gene expression

Abstract: Abstract. Serial analysis of gene expression (SAGE) is a sequence-based tool that enables quantitative study of comprehensive gene expression profiles. In this study, we generated a SAGE library of hepatitis B virus (HBV)-associated small hepatocellular carcinoma (HCC) and compared it with libraries of normal liver and other organs in order to identify genes which are specifically expressed in HBV-associated small HCC. A total of 18,107 SAGE tags were obtained from the HCC SAGE library. Among the 7,405 unique … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 39 publications
1
7
0
Order By: Relevance
“…Serum response factor has been reported to be involved in promoting the carcinogenesis and progression of colorectal cancer (6), hepatocelluar carcinoma (7,8,10,11), breast cancer (5) and thyroid carcinoma (9). However, the role of SRF in ESCC and its mechanism of action have not been reported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Serum response factor has been reported to be involved in promoting the carcinogenesis and progression of colorectal cancer (6), hepatocelluar carcinoma (7,8,10,11), breast cancer (5) and thyroid carcinoma (9). However, the role of SRF in ESCC and its mechanism of action have not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…A number of researchers have reported that SRF is highly expressed in tumors, including colorectal cancer (6), hepatocelluar carcinoma (7,8), breast cancer (5) and thyroid carcinoma (9). Overexpression of SRF in hepatocellular carcinoma and breast cancer accelerates cell migration and invasion, and there is a subsequent acquisition of mesenchymal phenotypes due to the expression of a mesenchymal marker (vimentin) (5,10).…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that LCN2 is synthesized in the cirrhotic liver (Takahara et al 2006;Kim et al 2009), and that LCN2 forms a complex with 92-kDa gelatinase (MMP-9) in the urine of certain cancer patients (Kjeldsen et al 1993;Yan et al 2001). Urine samples have been scarcely studied to identify liver fibrosis markers, and we were able to identify only one experimental report that analyzed urine samples with respect to hepatic fibrosis (Smyth et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Elevated LCN2 is not liver disease-specific: LCN2 is elevated in various clinical conditions such as bacterial infection and other co-morbidities that can elicit a systemic inflammatory response (Xu and Venge 2000). Moreover, LCN2 is elevated in several cancers including hepatocellular carcinoma (Bratt 2000;Kim et al 2009) and acute or chronic kidney injury (Mishra et al 2004;Mishra et al 2006;Bolignano et al 2009). Although we excluded these possibilities in our subjects, these are limitations for the use of LCN2 as a potential marker for hepatic fibrosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation